Cystic Fibrosis: A Review of Current Knowledge, Treatment Methods and Diagnostics - Wdowiak, Natalia; Choinka, Martyna; Konopka, Agata; Szczepaniak, Zuzanna; Adamska, Kinga; Kaczmarek, Aleksandra (Quality in Sport, 2024)
Introduction: Cystic fibrosis (CF) is an autosomal recessive genetic disease caused by a mutation in the CFTR gene. Characteristic symptoms include persistent lung infection, pancreatic insufficiency, and elevated sweat chloride, although many patients have mild or atypical symptoms. Diagnosis of CF is based primarily on the detection of genetic and/or functional abnormalities in the CFTR gene. Treatment includes pancreatic enzyme replacement therapy, mucolytic drugs, respiratory physiotherapy, and antibiotic therapy. Purpose of the work: This study aims to review and characterize the clinical and pathophysiological aspects of cystic fibrosis. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: Cystic fibrosis, CFTR, Chloride Channels, Lung Inflammation, Diagnosis, Gene therapy, Treatment. Results: Cystic fibrosis is the most common, multisystem, life-threatening recessive disease in the white race. Although many organs are affected, the leading cause of morbidity and mortality is lung disease. Treatment requires pharmacotherapy, extensive physiotherapy, and nutritional support. In recent years, there has been significant progress in the diagnosis and treatment of cystic fibrosis, and the average survival has increased from a few to almost 50 years.